Mediality in the Middle Ages abundance and lack - Kiening, Christian 1962- (Medieval media cultures, 2019)
In medieval culture, media forms were places of mediated immediacy. They transported a presence of the divine, but also knowledge of its unattainability. This volume investigates the multi-layered and fascinating approaches of medieval authors to the word and writing, the body and materiality, and their experimentation with the possibilities of media before the concept was invented. The book presents, for the first time, a coherent, tightly argued history of medieval mediality, which also casts a new light on modern thinking about the medial